Development and characterization of ZnO thin film for piezoelectric applications. (2020) - Kumar, Ashish; Saini, Surendra Kumar; Sharma, Girraj; Johar, Arun Kishor
Abstract: This paper reports a structural study of the ZnO thin film deposited on p -type silicon substrate using radio frequency (RF) sputtering technique. The structural study of the deposited ZnO thin film is done. The X-ray diffraction (XRD) spectra shows a strong peak of (0 0 2) orientation which ensures high quality of piezoelectric film. The roughness of the ZnO film is measured and found to be 1.85 nm which attributed to lower acoustic loss during wave propagation. These sputtering parameters can be used to deposit good quality ZnO thin film which can be utilized as piezoelectric layer in acoustic sensors, pressure sensors and many other optoelectronics devices.